Chronic paternal alcohol exposures induce dose-dependent changes in offspring craniofacial shape and symmetry - Higgins, Samantha L.; Bhadsavle, Sanat S.; Gaytan, Matthew N.; Thomas, Kara N.; Golding, Michael C. (Frontiers in Cell and Developmental Biology, 2024)
Although dose-response analyses are a fundamental tool in developmental toxicology, few studies have examined the impacts of toxicant dose on the non-genetic paternal inheritance of offspring disease and dysgenesis. In this study, we used geometric morphometric analyses to examine the impacts of different levels of preconception paternal alcohol exposure on offspring craniofacial shape and symmetry in a mouse model. Procrustes ANOVA followed by canonical variant analysis of geometric facial relationships revealed that Low-, Medium-, and High-dose treatments each induced distinct changes in craniofacial shape and symmetry. Our analyses identified a dose threshold between 1.543 and 2.321 g/kg/day. Below this threshold, preconception paternal alcohol exposure induced changes in facial shape, including a right shift in facial features. In contrast, above this threshold, paternal exposures caused shifts in both shape and center, disrupting facial symmetry. Consistent with previous clinical studies, changes in craniofacial shape predominantly mapped to regions in the lower portion of the face, including the mandible (lower jaw) and maxilla (upper jaw). Notably, high-dose exposures also impacted the positioning of the right eye. Our studies reveal that paternal alcohol use may be an unrecognized factor contributing to the incidence and severity of alcohol-related craniofacial defects, complicating diagnostics of fetal alcohol spectrum disorders.